UMP set up fund for Japan’s triple disasters - UMP, PNC
In a show of solidarity and communal concern for Japan’s recent triple disasters, Universiti Malaysia Pahang (UMP) has set up a humanity aid fund on March 28 to help ease the suffering faced by the people from the Land of the Rising Sun.